Mankind and the Masculine Pleasures of Penance. (2nd January 2019) - Garrison, Jennifer
ABSTRACT: Through a close examination of the fifteenth-century morality play, Mankind, this article argues that scholarship should expand its current theoretical understandings of medieval penance. Mankind is a dramatization of and reflection on the three stages of sacramental penance (contrition, confession, and satisfaction) and its focus is decidedly gendered: it is a play performed by, for, and about men. Mankind shows how the penitential process enables men to achieve redemption through acknowledging not only their own individual failings but also the failure of contemporary definitions of masculinity. Drawing on psychoanalytic theory, this article demonstrates that Mankind invites its audience to recognize sin and penance as a compulsive cycle; the play asks its audience to experience a sort of pleasure in recognizing that every Christian man participates in an endless cycle of sin and penance, a cycle that necessarily undermines a masculine identity based on self-sufficiency. Through its scatological and obscene humor — specifically the play's association of the anus with both materiality and sin — Mankind presents penance as an opportunity for men to recognize and celebrate the contingent and socially dependent nature of masculine identity.